Sport development in action plan, programme and practice - Astle, Alec; Leberman, Sarah; Watson, Geoff 1969- (Routledge, 2019)
This practical textbook explains the sport development process from a practitioner's viewpoint, showing what actually works, how, and why. Focusing on the development of sport, the book considers the efforts of sport organisations to revitalise their sports at a community level to ensure their future relevance, growth, and sustainability. Full of real-world cases and data, as well as the voices and reflections of a wide range of practitioners, Sport Development in Action explains how to research and draw up a development plan, how to design and implement programmes and establish delivery networks, and how to monitor and evaluate initiatives. This is essential reading for any sport development course, and useful reading for courses in sport management, sport coaching, or sports studies. It is also an indespensable reference book for practitioners.